ЛАКТОБАКТЕРИЯЛАРДЫҢ БЕЛСЕНДІ ШТАМДАРЫ НЕГІЗІНДЕ СҮТҚЫШҚЫЛДЫ СУСЫН АЛУ (Experimental biology, 2017)
It is studied biotechnological valuable properties of Lactobacteria, allocated from various substrates and on the basis of active strains were received a lactic beverage.
Keywords: Lactobacteria